Mid-infrared luminescence from coupled quantum dots and wells - Shields, P; Li, L; Nicholas, R (2004)
Coupled nanostructures have been developed in the InAs/InSb/GaSb materials system in order to extend the emission wavelength further into the infrared, beyond 2 mum. The samples studied consist of a single narrow InAs quantum well grown below a layer of InSb quantum dots in a GaSb matrix, in which the coupling has been altered by changing the thickness of a GaSb spacer layer. The overall transition energy of the combined dot-well system is generally reduced with respect to the dots and well only but the dependence on spacer thickness is more complex than that expected from a simple envelope function model. (C) 2003 Elsevier B.V. All rights reserved.